Lmo3 deficiency in the mouse is associated with alterations in mood-related behaviors and a depression-biased amygdala transcriptome. (January 2020) - Reisinger, Sonali N.; Bilban, Martin; Stojanovic, Tamara; Derdak, Sophia; Yang, Jiaye; Cicvaric, Ana; Horvath, Orsolya; Sideromenos, Spyros; Zambon, Alice; Monje, Francisco J.; Boehm, Stefan; Pollak, Daniela D.
Highlights: Lmo3 deficiency is associated with alterations in emotional behavior. Absence of Lmo3 impairs amygdala LTP. Amygdala transcriptome is selectively altered in Lmo3-deficient mice. Abstract: The highly conserved transcription factor LIM-only 3 (Lmo3) is involved in important neurodevelopmental processes in several brain areas including the amygdala, a central hub for the generation and regulation of emotions. Accordingly, a role for Lmo3 in the behavioral responses to ethanol and in the display of anxiety-like behavior in mice has been demonstrated while the potential involvement of Lmo3 in the control of mood-related behavior has not yet been explored. Using a mouse model of Lmo3 depletion ( Lmo3 z ), we here report that genetic Lmo3 deficiency is associated with altered performance in behavioral paradigms assessing anxiety-like and depression-like traits and additionally accompanied by impairments in learned fear. Importantly, long-term potentiation (LTP) in the basolateral amygdala (BLA), a proposed cellular correlate of fear learning, is impaired in Lmo3 z mice. RNA-Seq analysis of BLA tissue and gene set enrichment analysis (GSEA) of differentially expressed genes in Lmo3 z mice reveals a significant overlap between genes overexpressed in Lmo3 z mice and those enriched in the amygdala of a cohort of patients suffering from major depressive disorder. Consequently, we propose that Lmo3 may play a role in the regulation of gene networks that are relevant to the regulation of emotions. Future work may aid to further explore the role of Lmo3 in the pathophysiology of affective disorders and its genetic foundations.